The development of a prototype kiosk program and its potential for use in the UP Law Library - Romero, Robert Matthew C.; Cabbab, Johann Frederick A. (Quezon City Institute of Library Science, University of the Philippines Diliman, 2002)
The study aimed at developing a prototype-kiosk program and determining its potential for use in the UP Law Library. The study also aimed at determining which features of the prototype-kiosk program were useful to the respondents. Finally, it looked into the general attitude of the users towards the existence of such devices inside libraries. The development of the program underwent several stages namely: planning, requirements analysis, architecture design, storyboarding, content production, authoring and evaluation. In determining user reaction towards the program, a structured questionnaire was sampled, revised, and distributed to 75 library users.
The survey was conducted at the third floor, Reserve section of the aforementioned library during the period March 11 to 17, 2002. The respondents' answers were then tabulated, and percentages calculated. Afterwards, all the responses were analyzed. Major findings of the study were: 1) Most of the library users sampled were students (94.67 percent) attributing to the age bracket that most of the respondents fall into: 21 to 30 years old (85.33 percent). 2) Most of the respondents were familiar with the library (22.67 percent were very familiar 62.67 percent are averagely familiar), since 68 percent of them visit the library at least once a day. 3) For queries inside the library, the respondents generally refer to the librarian for assistance because the librarian is most knowledgeable inside the premises. 4) An overwhelming 71 (94.66 percent) respondents of the sample population of 75 have a positive reaction toward the kiosk program finding the program interesting, informative, and easy to understand. These findings coincided with the top two characteristics that the respondents feel information-kiosks should possess--that it should be user friendly and informative. 5) 73 (97.33 percent) of the surveyed population found the program useful, particularly the quick find, facilities and site map as the most useful among the features of the program.
In conclusion, kiosk-type products employing the use of multimedia holds much potential for use and acceptance in the library setting. It is the recommendation of this study that applications of multimedia kiosks in the different library units be looked into and further developed.
Vita.
Thesis (Bachelor of Library and Information Science)
Keywords: University of the Philippines College of Law Library; Library planning